Casuistry of an Emergency Service: Reasons for Referencing Primary Health Care - Santos, Inês Vieira; Escária, Susana; Piteira, Maria; Calçada, Sofia; Canudo, Diogo; Oliveira, Alicia; Guz, Claudiu; Lino, Ireneia (Portuguese Journal Internal Medicine, 2021)
Introduction: A large number of patients from primary health care are referred to the hospital emergency department daily. The aim of our study is to identify the major reasons for that, the approach in the emergency department and the destination of these patients. Material and Methods: Descriptive study. All patients from primary health care (PHC) were selected at ARS Alentejo Central, referred to the emergency department (ED) of Hospital Espírito Santo de Évora, for the specialty of Internal Medicine, in the month of January and July 2017. To perform the statistical analysis, the Speed Statistics® (SPSS) was used. Results: About 15% of patients admitted to the emergency department are from PHC and 50% of these are forwarded for internal medicine. About 57% of patients have priority and the most frequent reason for referral is respiratory symptoms. A major conclusion carries out complementary diagnostic tests. It was found that 75% of the admitted patients were discharged to the home, 25% of whom had no acute pathology or had not been diagnosed in the ED. Discussion and Conclusion: More studies are necessary to identify the gaps in the path of the patient with acute pathology and what motivates the transfer of patients from PHC to ED. It is necessary to reflect and change the strategy, with the objective of improving the efficiency of the national health system, culminating in greater comfort for the patient. It would also be attractive to make multidisciplinary teams, in support of PHC, to discuss cases of acute pathology and decide on the best diagnostic and therapeutic approach. In this way, it would be possible to reduce the consumption of resources, creating a more patient-centred approach.